STUDI LITERATUR TENTANG ILM AL-TAFSĪR KARYA ‘AFIFUDDIN DIMYATI DAN OBJEKTIVITAS EKSPLANASI ARGUMEN TAFSIR SAINS - Adjie Wahyu Kembara (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2024)
‘Ilm al-Tafsīr: Uṣūluhu wa Manāhijuhu by ‘Afīfuddīn is a book that compiles various topics in the discipline of tafsir (Quranic exegesis), one of which is the methodologies of tafsir. Regarding the topic of tafsir methodologies, an interesting fact is found in ‘Afīfuddīn's exposition of the model of scientific interpretation. ‘Afīfuddīn appears objective when presenting arguments from both pro and contra groups of scientific interpretation, and he even constructs a reconciliation argument between the two opposing groups. Based on this fact, the question arises: how does ‘Afīfuddīn explain the arguments put forward by both groups and his efforts at reconciliation in ‘Ilm al-Tafsīr? This question is important because in his tafsir book, Hidāyah al-Qur’ān, ‘Afīfuddīn seems to adhere to the model of interpreting the Qur'an with the Qur'an. Using a literary study and interpretive analysis approach, this study indicates that ‘Afīfuddīn's explanation of the pro and contra arguments of scientific interpretation is objective and tolerant but still adheres to the basic principles of interpretation. ‘Afīfuddīn's efforts in reconciling various arguments of scientific interpretation imply his wise and objective attitude as an intellectual. ‘Ilm al-Tafsīr: Usūluhu wa Manāhijuhu karya ‘Afifuddin merupakan kitab yang menghimpun topik-topik kajian dalam disiplin ilmu tafsir, salah satunya adalah manāhij al-tafsir. Mengenai topik kajian manhaj tafsir ini ditemukan fakta menarik dalam pemaparan ‘Afifuddin terhadap model penafsiran sains. ‘Afifuddin terlihat objektif saat memaparkan argumentasi dari kelompok pro maupun kontra tafsir sains, bahkan ia juga mengkonstruk argumen rekonsiliasi antara kedua kelompok yang berseberangan. Atas dasar fakta ini, timbul pertanyaan, bagaimana eksplanasi ‘Afifuddin terhadap argumen yang diusung oleh kedua kelompok serta upaya rekonsiliasinya dalam ‘Ilm al-Tafsīr? Pertanyaan ini menjadi penting karena ‘Afifuddin dalam kitab tafsirnya Hidāyah al-Qur’ān terlihat setia pada model penafsiran al-Qur’ān bi al-Qur’ān. Dengan pendekatan studi literatur dan analisis interpretasi, kajian ini mengindikasikan bahwa eksplanasi ‘Afifuddin terhadap pro-kontra argumen tafsir sains bersifat objektif dan toleran namun tetap berpegang teguh pada prinsip-prinsip dasar penafsiran. Upaya ‘Afifuddin dalam merekonsiliasi berbagai argumen tafsir sains menyiratkan sikapnya yang bijak dan objektif sebagai seorang intelektual.